Disillusionment with Postcolonial Experience in God's Own Land - khurshid Alam (بازیافت, 2021)
Khuda ki Basti ( God’s Own Land) is arguably the first novel in Urdu Language which problematizes the nature of postcolonial experience. Freedom came with a heavy price in this part of the world. Thousands of natives got displaced, killed and tortured on their way towards the newly born state of Pakistan. Hence migration remains the central trope in postcolonial literature and theory. The present study explores the nature of postcolonial experience by relying on the postcolonial theory. The main argument of the paper is that the process of othering finds new expression in the class division in the postcolonial social reality. In the colonial India, Hindu Muslim binary served to define “other”. But after decolonization, the religious ideology is replaced with economic determinism and the wretched of the earth like Nausha, Sultana and others feel disillusioned with postcolonial experiecne. And my argument is that Siddiqui finds an alternative to migration when his characters leave one place for another in search of prosperity and survival and end up as the social refuse existing at margins. Hence the reader also shares disillusionment with postcolonial experience.